Hubungan Tingkat Pendidikan Guru Terhadap Kinerja Guru Pendidikan Anak Usia Dini - Novitasari, Yesi; Fatmawati; Danang Prastyo (Institut Agama Islam Negeri Madura, 2024)
This study aims to determine the relationship between the level of teacher education and the performance of Early Childhood Education (ECE) teachers. The type of research is correlation research with two variables. The method used in drawing this sample is total sampling, which is a sampling technique where the number of samples is the same as the population. The reason for taking total sampling is because the population is less than 100. The sample taken from this study was 40 people. The results showed that ECE teachers in making lesson planning, implementing learning and evaluating learning in the dominant always namely 53.17% and included in the moderate category, meaning that Early Childhood Education teachers do not have good performance in carrying out their duties at school. The implication of the research results, ECE teachers should continue their education according to their field of expertise, in order to create suitability and good performance in the field of PAUD science.